Electrochemical Oxidative Csp3—H/S—H Cross‐Coupling with Hydrogen Evolution for Synthesis of Tetrasubstituted Olefins. Issue 6 (15th April 2019) - Lu, Fangling; Yang, Zengzhuan; Wang, Tao; Wang, Tianhao; Zhang, Yuying; Yuan, Yong; Lei, Aiwen
Summary of main observation and conclusion: Tetrasubstituted olefins are significant scaffolds as they are prevalent in many biologically active compounds and versatile building blocks for organic synthesis. Herein, we report an electrochemical oxidative Csp 3 —H/S—H cross‐coupling reaction, in which various tetrasubstituted olefins were prepared under base‐free, transition metal‐free, and oxidants‐free reaction conditions. Abstract : A series of tetrasubstituted olefins were prepared under base‐free, transition metal‐free, and oxidant‐free electrochemical conditions.